DIGRAF EKSENTRIS PADA DIGRAF SIKEL, DIGRAF KOMPLIT DAN DIGRAF KOMPLIT MULTIPARTIT - K, Retno Catur; Ratnasari, Lucia (MATEMATIKA, 2008)
The eccentric digraph of a digraph, , is the digraph that has the same vertex set as and the arc set defined by: there is an arc from to if and only if is an eccentric vertex of . In this paper, we examine eccentric digraphs of digraphs of varoius families of digraphs and we consider the behaviour of an iterated sequence of eccentric digraphs of a digraph.